Impact of Climate Change on Water Resources and Ecological Sustainability in Morocco: A 1990–2022 Analysis - Redouane Kaiss; Zakaria Benjouid; Nawal Snoussi; El Khalil El Mountassir; Nadia Nabil; Amal Halim; Said Saghir Zarouali (Research in Ecology, 2025)
This study comprehensively examines the multifaceted impact of climate change on Morocco’s ecological sustainability and economic development, focusing on four critical environmental stressors: water stress, deforestation, greenhouse gas emissions, and rising temperatures. These interrelated factors contribute significantly to the degradation of natural ecosystems, the decline in biodiversity, reductions in carbon sequestration, and the disruption of ecological balance. Water scarcity—exacerbated by declining precipitation, excessive groundwater extraction, and rising evapotranspiration—threatens the functionality of wetlands, agricultural productivity, and the livelihoods of rural populations. Deforestation accelerates soil erosion, alters hydrological cycles, and leads to the loss of critical habitats, while greenhouse gas emissions and temperature rise intensify climate variability and increase the frequency of extreme events such as droughts and heatwaves. Using longitudinal data from the World Bank (1990–2022) and advanced econometric modeling through EViews 12 software, this study reveals that water stress and rising temperatures have a statistically significant and negative impact on GDP, indicating that climate pressures undermine Morocco’s economic performance, particularly in climate-sensitive sectors. Conversely, the findings show that deforestation and greenhouse gas emissions are positively correlated with short-term economic growth, reflecting a development pattern heavily reliant on natural resource exploitation and carbon-intensive activities, which may offer temporary gains but pose serious long-term risks to sustainability. These results underscore the urgent need for a paradigm shift toward ecosystem-based adaptation and mitigation strategies, including afforestation, wetland restoration, integrated land and water resource management, and the incorporation of climate resilience into national development frameworks.